NAHDLATUL ULAMA IN FACING THE GUIDE DEMOCRACY 1959-1965: An Overview of Social and Political Factors - Hidayat, Asep Achmad; Nurjaman, Andri; Ahmad, Jafar; Witro, Doli; Alghani, Raid (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2022)
ABSTRACT Nahdlatul Ulama is one of the Islamic political parties that took part in the national political arena during President Soekarno's time from parliamentary democracy to the transition period from parliamentary democracy to guided democracy. NU's progress was closely related to its social and political factors which required NU to accept and integrate into President Soekarno's new government system. This paper aims to reveal the social and political factors that enabled NU to face and then accept guided democracy. This article employed a qualitative approach, particularly the historical study method. In tracing the socio-religious history in this study, the stages of heuristics, criticism, interpretation and historiography were taken. The results showed that NU's social factors in dealing with guided democracy were due to the presence of the PKI which was so strong in national politics and so close to President Soekarno. To deal with the PKI, like it or not, NU had to enter the government in order to resist the PKI and divert President Soekarno's inclination towards NU. Meanwhile, the political factor was to maintain NU's position in government, where had always received a share. NU efforts were done solely to protect Muslims, especially ahlussunnah waljamaah an-nahdliyah. Keywords: Guided Democracy, Nahdlatul Ulama, Socio-Political Factors. ABSTRAK Nahdlatul Ulama merupakan salah satu partai politik Islam yang berkiprah di kancah perpolitikan nasional masa Presiden Soekarno sejak demokrasi parlementer bahkan mampu bertahan pada masa transisi dari demokrasi parlementer ke demokrasi terpimpin. Hal ini karena ada faktor sosial dan politik yang mengharuskan NU menerima dan masuk pada sistem pemerintahan baru Presiden Soekarno. Tulisan ini bertujuan untuk mengungkap faktor sosial dan politik yang memungkiakan NU menghadapi dan kemudian menerima demokrasi terpimpin. Artikel ini menggunakan pendekatan kualitatif, dengan metodi studi sejarah. Dalam menelusuri sejarah sosial keagamaan dalam penelitian ini, ditempuh tahapan heuristik, kritik, interpretasi dan historiografi. Hasil penelitian menunjukan bahwa faktor sosial NU dalam menghadapi demokrasi terpimpin karena adanya eksistensi PKI yang begitu kuat dalam politik nasional dan kedekatannya dengan Presiden Soekarno. Untuk menghadapi PKI maka NU mau tidak mau harus masuk dalam pemerintahan dalam rangka membendung PKI dan mengalihkan kecenderungan Presiden Soekarno kepada NU. Sedangkan faktor politik adalah untuk mempertahankan kedudukan NU di pemerintahan yang sejak zaman demokrasi parlementer NU selalu mendapatkan jatah, hal ini dilakukan semata-mata untuk menjaga dan melindungi umat Islam khususnya ahlisunnah waljamaah an-nahdliyah. Kata kunci: Demokrasi Terpimpin Faktor Sosial-Politik, Nahdlatul Ulama.